HUBUNGAN PELAKSANAAN TUGAS KESEHATAN DAN DUKUNGAN KELUARGA DENGAN PENGABAIAN LANSIA DI WILAYAH KERJA PUSKESMAS KASSI-KASSI MAKASSAR - Nurlina Subair; Risma Haris (UNM Environmental Journals, 2021)
The research aims to determine the relationship between the implementation of health tasks and family support with the neglect of the elderly in the Kassi-Kassi Makassar Health Center work area. Correlation descriptive research design, cross sectional approach. Cluster sampling, totaling 223 respondents. The research sample is a family with elderly family members. Statistical tests used chi square and Logistic Regression. The results of the study stated that there was no relationship between the implementation of family health tasks and the neglect of the elderly. There is a relationship of information, instrumental, appreciation, and emotional support with the neglect of the elderly. Dominant emotional support is associated with neglect of the elderly. It was concluded that the elderly need support from the family, especially emotional support so that they can avoid incidents of neglect of the elderly in the family.